Evaluation of Antifungal Effect of Biodegradable Nano Encapsulated Extract of Trichoderma harzianum - M. Shahiri Tabarestani (Majallah-i ḥifāẓat-i giyāhān, 2022)
Introduction Chemical fungicides are widely used as effective control agents on a great diversity of fungal plant diseases. However, their excessive use, causes environmental pollution and health problems. Biological control as an environmentally friendly method can be a good alternative for chemical fungicides. Trichoderma is one of the antagonistic fungi with rapid adaptation to a wide variety of habitats. Trichoderma harzianum is a powerful agent for biocontrol of plant pathogens. It also can be used as a plant growth stimulant. However, its efficacy can be affected by biotic and abiotic factors, and encapsulation has been used to maximize its efficacy. Encapsulation process provides a protective barrier around the biocontrol agent, so the harmful external factors such as pH, humidity, and ultraviolet radiation do not damage its action. Encapsulation of the bioactive agents has been developed in recent years as a new potential tool for ecological and sustainable plant production. Encapsulation in biopolymer matrices has been recognized as an effective method for controlled release of a bioactive agent used for plant protection. Chitosan, the deacetylated derivative of chitin polysaccharide is one of the most important biopolymers that is widely used in biological and medical sciences especially for encapsulating essential oils and extracts due to its biocompatibility, low toxicity and biodegradability into safe byproducts. In this study, antifungal effects of nano capsulated Trichoderma extract (NCTE) and Trichoderma extract (TE) against Macrophomina phaseolina have been investigated.Materials and Methods The nanocapsules were prepared by ionic gelation method. This is one of the most advantageous techniques for the production of nanocapsules. This technique is easy to perform and avoids the use of organic solvents. The biocompatible and biodegradable polymer, chitosan, was used as a capsule coating agent. After extraction of T. harzianum secondary metabolites, encapsulation process was carried out. Tripolyphosphate was used as cross-linking agent in the encapsulation process. The surface morphology of the nanoparticles was considered using Field Emission Scanning Electron Microscopy (FE-SEM). The mean particle sizes of the prepared nanoparticles were measured by Dynamic Light Scattering (DLS) technique. For consideration of the antifungal effects of nano encapsulated Trichoderma extract (NCTE) and Trichoderma extract (TE) against Macrophomina phaseolina, strile potato dextrose agar (PDA) containing different concentrations of NCTE and TE were prepared. After 5 days, colony diameter of the pathogen was measured in all treatments. The inhibitory effect was calculated compared with the control. Data were statistically analyzed by SAS software.Results and Discussion The obtained results indicated that the prepared nanoparticles were spherical in shape and the average size was equal to 77.91 nm with poly dispersity index (PDI) 0.23554. PDI value indicated the physical stability of the nanoparticles and prevented aggregation of the particles. Antifungal effects of NCTE and TE were observed in all treatments, however nanocapsules contains Trichoderma extract were more effective than Trichoderma extract. In each treatment containing TE and NCTE, maximum inhibitory effect was related to concenteration of 30 percent. In consideration of ihibition percent of NCTE and TE on M. phaseolina within 5 days, it was found that on the first and second days, inhibitory effect of TE was more than NCTE. However, on the third, fourth and fifth days, there were no statistically significant difference between treatments in TE while in NCTE, a significant increasing was observed. The reason for the high inhibition percent in TE treatment in the first and second days was related to rapid release of active ingredients in the culture medium and the passage of time had no effect on improving its yield. According to the results in this research, it can be concluded that chitosan nanoparticles will be a good carrier for Trichoderma extract encapsulation. It also improves their antifungal activity against M. phaseolina.Conclusion Nano-encapsulation of the bioactive compounds enhances physical stability, protects them from oxidation process, controlling their release, improves water dispersion of hydrophobic compounds and enhances their bioactivity efficacy. In this study, nano encapsulation of Trichoderma extract, increased its antifungal effects over time. Nano encapsulated particles containing antagonistic fungi were able to control the pathogenic fungus more effectively and in a longer period of time due to the controlled release of the fungal extract. Results showed that antifungal efficiency of T. harzianum was increased by nano encapsulation procedure. Since chitosan is a biodegradable polymer without any harms for safety, this technique can be suggested as a good candidate for biological control. Our future investigations are directed to test nanocapsules simultaneously loaded with biological agents on M. phaseolina under greenhouse and field conditions.